Perbaikan Mutu Kualitas dan Daya Saing Produk Pada Sisi Kemasan Susu Kedelai Madu di UD Sehat Sejahtera Jember - Syaiful Bachri; Avisenna Harkat; Fredy Eka Ardhi Pratama; Aditya Wahyu Winadi Atmajaya; Adityo Adityo (Journal of Community Development, 2025)
This community service activity aims to improve the quality and competitiveness of honey soy milk products at "UD Sehat Sejahtera" Jember through packaging innovation. This activity is in line with the Jember State Polytechnic P3M program which focuses on strengthening agro-industry using local raw materials. In this activity, the service team identified that the plastic packaging currently used has many shortcomings, both in terms of durability and environmental impact. Therefore, innovation was carried out by changing the packaging to PET bottles which are more environmentally friendly and able to maintain product quality for longer. This activity includes design and development of new packaging, training for workers regarding the production process, as well as digital marketing strategies. The results of this activity are expected to increase the attractiveness of the product in the market, extend shelf life, and increase consumer satisfaction, thereby supporting the sustainability of the "UD Sehat Sejahtera" business in Jember.